2017
DOI: 10.1007/s11096-017-0468-9
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and severity of errors in pharmacist-written discharge medication orders

Abstract: Background Errors in discharge prescriptions are problematic. When hospital pharmacists write discharge prescriptions improvements are seen in the quality and efficiency of discharge. There is limited information on the incidence of errors in pharmacists’ medication orders. Objective To investigate the extent and clinical significance of errors in pharmacist-written discharge medication orders. Setting 1000-bed teaching hospital in London, UK. Method Pharmacists in this London hospital routinely write discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, the technician TTO error rate was lower than doctors both in this audit, and average discharge error rates reported elsewhere (6.4%) 1. Similarly, the reported error rate for pharmacy technicians was higher than that (0.2%) reported for transcribed TTOs by pharmacists in a recent study 13. Such differences possibly reflect heterogeneity in prescribing error definitions with further research required to assess any difference that could inform future service design.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, the technician TTO error rate was lower than doctors both in this audit, and average discharge error rates reported elsewhere (6.4%) 1. Similarly, the reported error rate for pharmacy technicians was higher than that (0.2%) reported for transcribed TTOs by pharmacists in a recent study 13. Such differences possibly reflect heterogeneity in prescribing error definitions with further research required to assess any difference that could inform future service design.…”
Section: Discussionmentioning
confidence: 65%
“…Full electronic prescribing provides considerable promise to improve prescribing errors although benefits are not consistent21 and omission or commission errors can still occur on discharge for example. While the role of pharmacy technicians in TTO transcribing with full electronic systems is unknown, and is likely to vary or become redundant depending on the system used, a recent study reported low error rates from pharmacists transcribing discharge medications using full electronic systems 13. This demonstrates appetite, at least with some electronic systems, for non-medical transcribing of TTOs and provides possible future research avenues to compare error rates and the cost effectiveness of different staff groups undertaking this role.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that the preventable adverse events are a leading cause of death in the United State and at least 44,000 to 98,000 Americans are dying in the hospitals each year as a result of medical errors. National cost has been estimated to be between $37.6 billion and $50 billion for adverse events and between $17 billion and $29 billion for preventable adverse events in the USA (62). These estimations could always be lower than the actual figures due to under reporting of the incidents due to the fear of disciplinary actions (63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it has been shown that pharmacists can prescribe safely but despite this the longstanding practice, in most healthcare settings, has been to let the physician play the central role in prescribing. 39 In Australia, recent studies have shown that pharmacist-led interventions which include a partnered doctor-pharmacist prescribing have not only produced lower rates of medication errors but a reduced length of hospital stay (4.7 versus 4.2 days with p < 0.001) which in turn will lead to reduced healthcare costs. 40 In another Australian geriatric service, a collaborative pharmacist-led prescribing model for discharge prescriptions had fewer patients with MEs than the usual prescribing model in both handwritten and digital prescriptions.…”
Section: Effectiveness Of Interventions Relevant To Singaporementioning
confidence: 99%